Environmental Ethics: Nurturing Sustainable Development and Global Well-being (International Journal of Food and Nutritional Sciences, 2022)
This article delves into the core principles of environmental ethics and various ethical frameworks, such as biocentrism and ecocentrism. It examines the complex interplay among intrinsic worth, inherent value, instrumental value, and moral considerations within environmental ethics. Furthermore, it delves into the philosophical underpinnings of these concepts to elucidate their impact on our understanding of the environment and our ethical responsibilities toward it. Additionally, it addresses the challenges posed by speciesist anthropocentric attitudes and proposes strategies to overcome these biases. The article underscores the necessity of embracing environmental ethics to achieve sustainable development. It stresses the significance of holistic approaches that prioritize the well-being of ecosystems and non-human organisms alongside human interests. Moreover, it underscores the pivotal role of environmental ethics in guiding ethical decision-making and fostering harmonious relationships between humans and the natural world, grounded in thorough analysis.